The impact of pharmacological modulation of the NMDA-receptor/NO signalling pathway on neuronal complexity in vitro - O'Toole, Eileen (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2016)
Neuronal atrophy and alterations in dendritic and synaptic structure are associated with multiple central nervous system (CNS) disorders ranging from acute neurological injuries to chronic neurodegenerative diseases and neuropsychiatric illnesses. Excess glutamatergic neurotransmission is increasingly associated with several of these disorders and has been suggested to contribute to the observed neuronal atrophy and synapse loss. The detrimental effects of glutamate on neurons has been particularly associated with overactivation of the glutamate Nmethyl-D-aspartate receptor (NMDA-R), which couples to neuronal nitric oxide synthase (nNOS) and the nNOS adaptor protein 1 (NOSl AP) via the post-synaptic density 95 (PSD-95). An in vitro model composed of rat primary cortical neurons was used in this thesis to investigate the effects of glutamatergic modulation on neurite outgrowth as measured by Sholl analysis, and synapse number as measured by quantification of the co-localised expression of the pre-synaptic marker, synaptophysin and the post-synaptic marker, post-synaptic PSD-95.
Keywords: Pharmacy & Phamaceutical Sciences, Ph.D.; PhD Trinity College Dublin, 2016